COMPLIANCE RISK MANAGEMENT IMPLEMENTATION IN DIRECTORATE GENERAL OF TAXATION REPUBLIC OF INDONESIA - Tia Diamendia; Milla S Setyowati (Faculty of Economics and Business, Universitas Pasundan, Bandung, Indonesia, 2021)
The vast amount of taxpayer and the limited resources in Indonesian Tax Authority (DJP) to monitor the taxpayer, require DJP to plan tax audit optimally. This study aim to analyze the effectifity of Compliance Risk Management (CRM) policy in DJP. This study is using qualitative approach through interview with 7 peoples who have roles in implementing tax policy in Indonesia. This study founds the importance of CRM policy, in which the tax authority cannot apply the same treatment to all taxpayers, so it needs to decide which taxpayer needs to be investigated with rational justification based on risk level. Tax authority needs to focus on implementing CRM as an important source of information in decision making process.